2014
DOI: 10.1227/neu.0000000000000258
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Cardiac Complications and 30-Day Mortality in Patients Undergoing Intracranial Aneurysmal Surgery With Adenosine-Induced Flow Arrest

Abstract: Our results suggest that adenosine-assisted intracranial aneurysm surgery is not associated with an increase in perioperative cardiac complications or mortality in patients with low risk of coronary artery disease and may be considered a safe technique to assist clipping of complex aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
8

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 16 publications
1
39
0
8
Order By: Relevance
“…The studies have shown that 57 (24.7%) of 231 patients got adenosine during posterior circulation clipping, which include 25(10.8%) basilar artery aneurysm and 29(12.55%) unsorted posterior circulation aneurysm. This supports the fact that the surgeries in this area are generally more difficult, with deep and narrow corridor; thus they are technically more challenging [3,9,11,18,19] .…”
Section: Indications Of Using Adenosine-induced Flow Arrest For Complsupporting
confidence: 60%
See 1 more Smart Citation
“…The studies have shown that 57 (24.7%) of 231 patients got adenosine during posterior circulation clipping, which include 25(10.8%) basilar artery aneurysm and 29(12.55%) unsorted posterior circulation aneurysm. This supports the fact that the surgeries in this area are generally more difficult, with deep and narrow corridor; thus they are technically more challenging [3,9,11,18,19] .…”
Section: Indications Of Using Adenosine-induced Flow Arrest For Complsupporting
confidence: 60%
“…Of these 16 patients, 12 patients got 1 bolus, and 4 patients received multiple bolus. Median dose for a single injection was 12 mg (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), and the median total dose for multiple injections was 27 mg . Ten minutes after adenosine administration, all patients were hemodynamically stable, and 13 required vasoactive drugs during the procedure.…”
Section: Dose Of Adenosinementioning
confidence: 99%
“…The complication rate after RVP, which has to be weighed against the considerable risk of spontaneous rupture of the aneurysms treated in this series, appears to be comparable to or lower than that reported after administration of adenosine in retrospective studies (Table 4). 4,5,22 Adenosine is easy available and usable, but it is not predictable, if the cardiac arrest persists (up to 20% of the patients had no effect in a prospective trial 11 ) and depending on how long (most often 10-30 seconds); 3,5,18,25 with RVP the anesthesiologist has a device with on/off demand for a tailored induction of hypotension. Also, after adenosine application, hypotension persists longer (5-10 minutes) than after RVP, requiring vasoactive agents in some patients.…”
Section: Why Rvp and Not Adenosine?mentioning
confidence: 99%
“…Недостаточно прогнозируемыми остаются длительность асистолии, а также невозможность безопасного обеспечения двух и более ее последовательных эпизодов. Кроме того, нельзя забывать о феномене коронарного обкрадывания и бронхоспастическом потенциале препарата, следовательно, снижение коронарного резерва и наличие в анамнезе хронической обструктивной болезни легких должны быть относительными противопоказаниями к применению данного метода [95]. Соответственно необходимо быть готовым к развитию аритмологических, респираторных осложнений, коррекции длительности периода асистолии, брадикардии, стойкой гипотензии.…”
Section: аденозин-индуцированный транзиторный кардиальный арестunclassified